Elevated salinity and temperature associated with climate change threaten the survival and conservation of desert spring amphipods. Issue 3 (16th November 2021) - Burns, McKenna P.A.; O'Connell, Michael J.; Schaeffer, Paul J.; Berg, David J.
Abstract: Freshwater ecosystems are disproportionately rich in biodiversity and are threatened by anthropogenic change. In particular, desert springs often contain high levels of aquatic biodiversity and endemism. The Chihuahuan Desert is recognized as a priority ecoregion for global conservation for its high levels of taxonomic richness and because human activities have caused declines in the freshwater fauna of this region. Agricultural, industrial and domestic use of water, increased prevalence and severity of fire, and general environmental warming resulting from climate change threaten to increase the temperature and salinity of these arid‐land waters. Two species of amphipods, Gammarus colei and Hyalella sp., were used as models for understanding the effects of increased salinity and temperature on desert spring species. Both species are endemic to the same spring in the Chihuahuan Desert. A full‐factorial survivorship experiment was conducted that exposed individuals of both species to a range of temperatures (ambient and 25 and 30°C) and salinities (ambient and 10, 15 and 19 parts per thousand) that can be associated with disturbance events. Resting metabolic rates (V˙O2 ) were measured at elevated salinities. Both species were more likely to die at higher salinities, and G. colei had significantly lower survivorship at higher temperatures. Gammarus were as much as 200 times more likely to die at the highest experimental temperature and salinity conditions compared with ambient conditions. Metabolic rates varied with salinity: G. colei demonstrated a threshold response to increased salinity while Hyalella sp. did not. Whereas both species are sensitive to changes in salinity, G. colei is also sensitive to increased temperatures. Because climate warming will result in higher rates of evaporation, these and other endemic aquatic organisms are likely to be exposed to the combined effects of increased temperature and salinity. Climate change, combined with habitat alteration caused by other human activities, threatens the survival of the unique communities in desert aquatic systems.